Macrofauna bentônica associada aos recifes arenosos de sabellaria wilsoni (polychaeta, sabellariidae) na Ilha de Algodoal-Maiandeua (Pará, Brasil) - FARIAS, Raphael Simão de (2019)
This study aimed to characterize the macrobenthic associations with sandy reefs of Sabellaria wilsoni at Algodoal-Maiandeua island, in northeastern Pará State, among different morphologies (mushroom and platform), hydrodynamic conditions and climate periods relate to the end of rainy season (June) and end of dry season (December) 2008. At each reef were taken 16 samples, totaling 32 samples per month. The material was packed in plastic bags labeled and fixed in formalin 4%. The univariate (ANOVAs's and tukey tests over density, richness, diversity, evenness) and multivariate (ANOSIM, MDS and SIMPER over density matrix) analysis were performed to describe the structure of macrobenthic fauna associated with sandy reefs. This structure was distinct among months, which was composed by 93 taxa among 11 different phyla, with dominance of Annelida (40 taxa), Mollusca (24 taxa) and arthropods (17 taxa). The structure of the macrofauna was influenced by the structure and morphology of the reefs, which in turn were modified by seasonal variations of local hydrodynamics. Overall, reef platform, well developed in sheltered beach, shown a more diverse and equitable fauna in a estuarine and unconsolidated substrate which was dominated by wormlike species, especially during his well maintained state (June of 2008). The mushrooms reef fauna were more dense and rich, typical of marine areas of higher energy. The dominant taxa were Crustacea and Mollusca. The environmental factors, salinity, rainfall and especially the local hydrodynamic, seen to directly influenced changes at the morphology of the reefs, in the density and composition of its builders and in abundance and diversity of macrofauna.